2019
DOI: 10.3390/molecules24081489
|View full text |Cite
|
Sign up to set email alerts
|

Snake Venom Hemotoxic Enzymes: Biochemical Comparison between Crotalus Species from Central Mexico

Abstract: Snakebite envenoming is a serious medical problem in different areas of the world. In Latin America, the major prevalence is due to snakes of the family Viperidae, where rattlesnakes (Crotalus) are included. They produce hemotoxic venom which causes bleeding, tissue degradation and necrosis. Each venom has several enzymatic activities, producing different effects in the envenoming, doing its clinical effects difficult to study. Comparison between venom molecules is also difficult when different techniques are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 63 publications
3
27
0
Order By: Relevance
“…Contrary to our results, Soto et al [88] described that C. scutulatus venom lacks gelatinolytic activity. Also, a study performed by Roldán-Padrón et al [89] demonstrated that the venom caseinolytic activity of C. atrox is higher than that of C. m. nigrescens.…”
Section: Protease Substrate Preferencementioning
confidence: 98%
“…Contrary to our results, Soto et al [88] described that C. scutulatus venom lacks gelatinolytic activity. Also, a study performed by Roldán-Padrón et al [89] demonstrated that the venom caseinolytic activity of C. atrox is higher than that of C. m. nigrescens.…”
Section: Protease Substrate Preferencementioning
confidence: 98%
“…This synergism causes the joint effects of multiple toxins to assert greater effects than the sum of individual potencies [ 73 ], making trace amount of snake venom to be highly efficient and effective [ 73 , 74 ]. Such combinations of venom proteins often cause various symptoms of bleedings, tissue degradation, necrosis, and further complications in prey and bite victims [ 69 , 177 ] and improve the lethality of whole crude venom in contrast to individual components [ 73 , 178 ].…”
Section: Discussionmentioning
confidence: 99%
“…Rattlesnakes possess various different toxins from 10–20 protein families [ 7 , 30 , 40 , 41 , 42 ]. These families possess several enzymes, such as: L-amino acid oxidases (LAAO) [ 30 , 43 , 44 , 45 , 46 ], phosphodiesterase (PDE) [ 47 , 48 , 49 ], snake venom metalloproteases (SVMP) [ 50 , 51 , 52 ], serine proteases (SVSP) [ 44 , 53 , 54 , 55 ], phospholipases (PLA 2 ) [ 56 , 57 , 58 , 59 ].Additionally, rattlesnake venoms also contain nonenzymatic proteins like myotoxin a and its homologs [ 60 , 61 , 62 , 63 ], bradykinin-potentiating peptides and bradykinin-inhibitory peptide (BPPs and BIPs) [ 30 , 44 , 64 , 65 ], disintegrins (Dis) [ 3 , 44 , 45 , 55 , 66 , 67 , 68 ], cysteine-rich secretory proteins (CRiSPs) [ 2 , 45 , 55 , 62 ], and C-type lectins (CTL) [ 30 , 41 , 48 , 69 ]. It is not uncommon to have variation in venom composition within species [ 17 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…SVSPs are well-studied venom enzymes affecting generally the hemostatic system. Individually, they are not considered lethal, but they contribute to the toxic effect when combined with other proteins of the venom [39,40]. Fundamentally, SVSPs can be categorized into different subtypes depending on their mode of action to include thrombin-like enzymes, kallikrein-like, plasminogen activators, platelet aggregation inhibitors, protein-C activators and prothrombin activators [41].…”
Section: Composition Of Snake Venomsmentioning
confidence: 99%